The impact of climate change on heat-related mortality in six major cities, South Korea, under representative concentration pathways (RCPs) - Kim, Youngmin; Kim, Soyeon; Liu, Yang (Frontiers in Environmental Science, 2014)
Background: We aimed to quantify the excess mortality associated with increased temperature due to climate change in six major Korean cities under Representative Concentration Pathways (RCPs) which are new emission scenarios designed for the fifth assessment report of the Intergovernmental Panel on Climate Change (IPCC). Methods: We first examined the association between daily mean temperature and mortality in each during the summertime (June to September) from 2001 to 2008. This was done using a generalized linear Poisson model with adjustment for a long-term time trend, relative humidity, air pollutants, and day of the week. We then computed heat-related mortality attributable to future climate change using estimated mortality risks, projected future populations, and temperature increments for both future years 2041-2070 and 2071-2100 under RCP 4.5 and 8.5. We considered effects from added days with high temperatures over thresholds and shifted effects from high to higher temperature. Results: Estimated excess all-cause mortalities for six cities in Korea ranged from 500 (95% CI: 313-703) for 2041-2070 to 2,320 (95% CI: 1,430-3,281) deaths per year for 2071-2100 under two RCPs. Excess cardiovascular mortality was estimated to range from 192 (95% CI: 41-351) to 896 (95% CI: 185-1,694) deaths per year, covering about 38.5% of all-cause excess mortality. Increased rates of heat-related mortality were higher in cities located at relatively lower latitude than cities with higher latitude. Estimated excess mortality under RCP 8.5, a fossil fuel-intensive emission scenario, was more than twice as high compared with RCP 4.5, low to medium emission scenario. Conclusions: Excess mortality due to climate change is expected to be profound in the future showing spatial variation. Efforts to mitigate climate change can cause substantial health benefits via reducing heat-related mortality.